Reactive species regulation by interlayered Na+/H+ of titanate nanotubes decorated Co(OH)2 hollow microsphere for peroxymonosulfate activation and gatifloxacin degradation - Bin Zhou; Long Chen; Li, Fan; Weiliang Sun; Zhicheng Pan; Yumei Peng; Lian Qiu; Liu, Wen (Chinese Chemical Letters, 2023)
Emerging organic pollutants (EOPs) in water are of great concern due to their high environmental risk, so urgent technologies are needed for effective removal of those pollutants. Herein, a heterogeneous advanced oxidation process (AOP) of peroxymonosulfate (PMS) activation by functional material was developed for degradation of a typical antibiotic, gatifloxacin (GAT). The reactive species including sulfate radical (SO4•−) and singlet oxygen (1O2) in this AOP were regulated by interlayered ions (Na+/H+) of titanate nanotubes that supported on Co(OH)2 hollow microsphere. Both the Na-type (NaTi-CoHS) and H-type (HTi-CoHS) materials achieved efficient PMS activation for GAT degradation, and HTi-CoHS even exhibited a relatively high degradation efficiency of 96.6% within 5 min. Co(OH)2 was considered the key component for generation of SO4•− after PMS activation, while hydrogen titanate nanotubes (H-TNTs) promoted the transformation of peroxysulfate radical (SO5•−) to 1O2 by hydrogen bond interaction. Therefore, when the interlayer ion of TNTs transformed from Na+ to H+, more 1O2 was produced for organic pollutant degradation. H-TNTs with lower symmetry preferred to adsorb PMS molecules to achieve interlayer electron transport through hydrogen bonding, rather than electrostatic interaction of Na+ for Na-TNTs. In addition, the degradation pathway of GAT mainly proceeded by the cleavage of C–N bond at the 8 N site of the piperazine ring, which was confirmed by condensed Fukui index and mass spectrographic analysis. This work gives new sights into the regulation of reactive species in AOPs by the composition of material and promotes the understanding of pollutant degradation mechanisms in water treatment process.
Keywords: Antibiotic; Heterogeneous catalysis; Peroxymonosulfate activation; Singlet oxygen; Sulfate radical